PPARγ Regulates Genes Involved in Triacylglycerol Synthesis and Secretion in Mammary Gland Epithelial Cells of Dairy Goats - Hengbo Shi; Jun Luo; Jiangjiang Zhu; Jun Li; Yuting Sun; Xianzi Lin; Liping Zhang; Dawei Yao; Huaiping Shi (PPAR Research)
To explore the function of PPARγ in the goat mammary gland, we cloned the whole cDNA of the PPARγ gene. Homology alignments revealed that the goat PPARγ gene is conserved among goat, bovine, mouse, and human. Luciferase assays revealed that rosiglitazone enhanced the activity of the PPARγ response element (PPRE) in goat mammary epithelial cells (GMECs). After rosiglitazone (ROSI) treatment of GMECs, there was a significant (P<0.05) increase in the expression of genes related to triacylglycerol synthesis and secretion: LPL, FASN, ACACA, PLIN3, FABP3, PLIN2, PNPLA2, NR1H3, SREBF1, and SCD. The decreases in expression observed after knockdown of PPARγ relative to the control group (Ad-NC) averaged 65%, 52%, 67%, 55%, 65%, 58%, 85%, 43%, 50%, and 24% for SCD, DGAT1, AGPAT6, SREBF1, ACACA, FASN, FABP3, SCAP, ATGL, and PLIN3, respectively. These results provide direct evidence that PPARγ plays a crucial role in regulating the triacylglycerol synthesis and secretion in goat mammary cells and underscore the functional importance of PPARγ in mammary gland tissue during lactation.